Global Warming Mitigation Innovation Through Household Waste Management Becomes Eco-Enzyme: A Review - I Nengah Muliarta (Postgraduate, University of Mataram, 2024)
The dumping of fruit and vegetable waste into landfills contributes to an increase in methane gas that contributes to global warming. Waste materials in the form of fruits and vegetables can be used and processed into eco-enzymes. Fermented waste enzymes have a variety of benefits and add value to materials that have been tended to be wasted. This environmentally friendly enzyme has been utilized ranging from disinfectants, floor cleaners, dishwashers to liquid organic fertilizers. The production of eco-enzymes in addition to being able to reduce the volume of household waste, also contributes to the reduction of methane gas. During the fermentation process produces O3 (ozone) which is beneficial in maintaining ozone content in the atmosphere. This means that eco-enzyme production becomes an innovation in mitigating global warming from the household level. The manufacture of eco-enzymes is an effort to provide economic value to waste that has a positive impact on the environment and is a step to maximize the utilization of natural resources better known as circular economies. The advantages of eco-enzyme production in the short term are the ability to maximize raw materials and provide economic value and reduce the cost of handling household waste.